2001
DOI: 10.1089/088922201750290023
|View full text |Cite
|
Sign up to set email alerts
|

Virologic and Immunologic Determinants of Heterosexual Transmission of Human Immunodeficiency Virus Type 1 in Africa

Abstract: More than 80% of the world's HIV-infected adults live in sub-Saharan Africa, where heterosexual transmission is the predominant mode of spread. The virologic and immunologic correlates of femaleto-male (FTM) and male-to-female (MTF) transmission are not well understood. A total of 1022 heterosexual couples with discordant HIV-1 serology results (one partner HIV infected, the other HIV uninfected) were enrolled in a prospective study in Lusaka, Zambia and monitored at 3-month intervals. A nested case-control de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
281
6
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(305 citation statements)
references
References 52 publications
16
281
6
1
Order By: Relevance
“…In four other studies of HIV transmission in serodiscordant African couples (with most individuals not aware of their HIV status and/or with continuing unprotected sex), the unweighted average HIVincidence for men (women) was 7.6 (10.0) per 100 person years (PYs) 27± 30 , comparable to an incidence of 4.8± 7.2 per 100 PYs in European men and/or women with HIV-positive partners who continued unprotected sex 25,31,32 . Moreover, these data may overstate heterosexual transmission in African couples; a Zambian study that sequenced viruses to determine epidemiological linkage reported at least 13% of sequences in newly infected persons were not related to their partner's HIV 33 .…”
Section: Unexplained High Implicit Rates Of Heterosexual Transmissionmentioning
confidence: 99%
“…In four other studies of HIV transmission in serodiscordant African couples (with most individuals not aware of their HIV status and/or with continuing unprotected sex), the unweighted average HIVincidence for men (women) was 7.6 (10.0) per 100 person years (PYs) 27± 30 , comparable to an incidence of 4.8± 7.2 per 100 PYs in European men and/or women with HIV-positive partners who continued unprotected sex 25,31,32 . Moreover, these data may overstate heterosexual transmission in African couples; a Zambian study that sequenced viruses to determine epidemiological linkage reported at least 13% of sequences in newly infected persons were not related to their partner's HIV 33 .…”
Section: Unexplained High Implicit Rates Of Heterosexual Transmissionmentioning
confidence: 99%
“…Viral load is the single greatest risk factor for all modes of transmission. 35,36 Sexual transmission of HIV has been closely linked to viral load in the blood of the infected host, [37][38][39][40][41] which probably serves as a surrogate, albeit imperfect, for HIV concentration in the genital tract. 42,43 In addition to lowering plasma viral load to nearly undetectable levels, ART can decrease viral load in genital secretions, 44,45 although patients having a detectable semen HIV load may have no detectable virus in their blood plasma, highlighting the residual risk of HIV-1 transmission during unprotected intercourse.…”
Section: Introductionmentioning
confidence: 99%
“…8 Among adults, gender differences in heterosexual HIV infection rates have been attributed to various biological (immunologic, genetic, viral, and hormonal), social, and behavioral factors. [9][10][11][12][13][14][15] Among children, gender-specific differences could indicate inherent physiologic factors that influence not only differential progression of the disease but also acquisition of the virus as early as in utero. Few studies have observed more HIV infection among girls than boys.…”
mentioning
confidence: 99%